Sorption Equilibria of Heavy Metals on Polysiloxane with Grafted 2-Aminoethylpyridine Functional Groups - Zasuhin, A.S.; Neudachina, L.K.; Yatluk, Yu.G.; Osipova, V.A.; Moskaleva, Yu.S.; Muzipova, E.F.; Morozova, M.V.; Starcev, V.A. (Хімія, фізика та технологія поверхні, 2010)
A new silica-based organic-inorganic hybrid material with grafted 2-aminoethylpyridine functional groups (SiAEP) has been synthesized by sol-gel method. Methods of the elemental analysis, 13С and 1H NMR spectroscopy have been used in order to find substance composition; surface-structural characteristics of the SiAEP have been defined by method of nitrogen adsorption–desorption isotherms. The effect of pH on the sorption of copper (II), nickel (II), cobalt (II), zinc (II), cadmium (II), and lead (II) ions has been studied. A selectivity order of SiAEP at рН=6.5 is as follows: Cu>Co>Zn>Ni>Pb>Cd. Sorption isotherms of heavy metal ions by SiAEP have been obtained, their mathematical processing by models of Langmuir, Freundlich, and Redlich-Peterson has been carried out. The values of the maximum uptake SiAEP capacity for Cu2+, Co2+, Zn2+, Ni2+, and Cd2+ ions have been defined to be of 2.04, 1.76, 1.46, 1.06, and 0.76 mmol/g, respectively. Золь-гель методом синтезовано новий органо-неорганічний матеріал з прищепленими 2-аміноетилпіридиновими функціональними групами (SiAEP). Методи елементного аналізу, 13С та 1H ЯМР-спектроскопії використано для визначення складу речовини; структурно-адсорбційні характеристики SiAEP визначено за ізотермами адсорбції та десорбції азоту. Вивчено вплив pH на сорбцію іонів міді (II), нікелю (II), кобальту (II), цинку (II), кадмію (II) та свинцю (II). Ряд селективності SiAEP при рН=6,5 наступний: Cu>Co>Zn>Ni>Pb>Cd. Одержано ізотерми сорбції іонів важких металів за допомогою SiAEP, виконано їхню математичну обробку за моделями Ленгмюра, Фрейндліха та Редліха-Петерсона. Величини граничної адсорбції для іонів Cu2+, Co2+, Zn2+, Ni2+ та Cd2+ виявились рівними відповідно 2,04, 1,76, 1,46, 1,06 та 0,76 ммоль/г. Золь-гель методом синтезирован новый органо-неорганический материал с привитыми 2-аминоэтилпиридиновыми функциональными группами (SiAEP). Методами элементного анализа, 13С и 1H ЯМР-спектроскопии определен состав вещества; структурно-адсорбционные характеристики SiAEP определены по изотермам адсорбции и десорбции азота. Изучено влияние pH на сорбцию ионов меди (II), никеля (II), кобальта (II), цинка (II), кадмия (II) и свинца (II). Ряд селективности SiAEP при рН=6,5 следующий: Cu>Co>Zn>Ni>Pb>Cd. Получены изотермы сорбции ионов тяжелых металлов на SiAEP, проведена их математическая обработка по моделям Лэнгмюра, Фрейндлиха и Редлиха-Петерсона. Величины максимальной сорбционной емкости SiAEP по ионам Cu2+, Co2+, Zn2+, Ni2+ и Cd2+ составили соответственно 2,04, 1,76, 1,46, 1,06 и 0,76 ммоль/г.